Intractable chronic otitis media, rhinosinusitis and facial palsy: a case of active granulomatosis with polyangiitis. Issue 9 (7th September 2020) - Goh, Kwee Yen; Bannon, Ross; Darat, Helin Nie; Ram, Bhaskar; Dwivedi, Raghav C
Abstract : Granulomatosis with polyangiitis (GPA) is a rare systemic disease of unknown aetiology, characterised by necrotising granuloma formation and diffuse vasculitis. It typically affects the upper and lower respiratory tract in addition to the kidneys. Without treatment, the 2-year mortality rate exceeds 90%. We describe a presentation of intractable serous otitis media, rhinosinusitis, fever and unilateral facial palsy in an 18-year-old man with learning difficulties, which highlights the need for a high index of suspicion in diagnosing and treating this enigmatic disease.